Vitiligo: Correlation with cytokine profiles and its role in novel therapeutic strategies: A case-control study - Karishma Desai; Hari Kishan Kumar; S Naveen; Prabhakar Somanna (Wolters Kluwer Medknow Publications, 2023)
Background: The inflammatory and immune factors play a key role in the pathogenesis of vitiligo, and there are very few studies that have investigated the levels of major cytokines produced by T helper (Th) 1, Th2, and Th17 cells. This can enable better understanding of the, pathogenesis, and severity of vitiligo. Objectives: To evaluate the serum levels of interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-1β, interferon (IFN)-γ, and IL-10 in patients with vitiligo and to correlate them with the disease severity and activity and to compare them with normal healthy controls. Materials and Methods: A case-control study was conducted with 100 study participants: 50 cases clinically diagnosed as vitiligo and 50 controls. All patients underwent complete evaluation with detailed demographic parameters, history, and physical examination. The severity of the disease was assessed clinically by Vitiligo Area Scoring Index (VASI) and Vitiligo Disease Activity Score (VIDA). Blood investigations performed were IL-6, TNF-α, IL-1β, IFN-γ, and IL-10. Results: We observed significantly higher levels of serum IFN-γ levels in the patient group when compared with those of the normal controls (P = 0.002) and showed a positive correlation with the activity and severity of the disease with a significant VASI (P = 0.05) and VIDA score (P = < 0.001). The mean serum IL-10 (p < 0.001) in patients with vitiligo was significantly lower than that in the control group. There was no significant difference in the serum level of TNF-α level (P = 0.347), IL-6 (P = 0.365), and IL-1β (P = 0.362) between vitiligo and healthy controls. Conclusion: This study proved that high serum level of IFN-γ may be a risk factor for vitiligo progression and significantly low levels of IL-10, which has an anti-inflammatory role, suggesting that they could be used as a marker for assessing vitiligo activity and may open the way for further therapeutic approaches for vitiligo.